INDONESIAN HATCHERY REARED SEABASS LARVAE (Lates calcarifer), ASSOCIATED WITH VIRAL NERVOUS NECROSIS (VNN) - Zafran Zafran; T. Harada; I. Koesharyani I. Koesharyan; K. Yuasa; K. Hatai (Research Center for Fisheries, 1998)
Mass tuortality atuongs seabass larvae, Lates calcarifer, reared in hatcheries in East and Bali due to viral nervous necrosis were investigated. outbreaks of the disease occured from August to Novetnber 1997.